Factors associated with mothers not vaccinating their children against mumps in Japan. (August 2016) - Tsuchiya, Y.; Shida, N.; Izumi, S.; Ogasawara, M.; Kakinuma, W.; Tsujiuchi, T.; Machida, K.
Abstract: Objectives: In Japan, mumps immunization is not mandatory, and the prevalence of mumps immunization among eligible children is only about 30%, raising concerns about increased risk of meningitis, encephalitis and deafness caused by mumps. In 2011, to understand why families are not voluntarily immunizing their children against mumps, we surveyed mothers who were university graduates to examine the factors and barriers influencing mumps vaccination in Japan. Study design: A cross sectional design. Methods: We sent questionnaires including questions on demographic data and vaccination status, barriers and factors for immunizations to university alumnae to recruit participants. Data were analysed by Student's t -test for continuous variables and by univariate and multivariate analysis to obtain the odds ratio and adjusted odds ratio. Results: Two hundred and twenty-six mothers with children responded with an average (range) age of 44.7 years (SD = 5.02; 30–55 years). Adjusted odds ratios (aOR) from logistic regression analysis identified fear of harmful side-effects (aOR, 2.55; 95% CI, 1.10 to 5.89), the vaccination not being mandatory (aOR, 3.30; 95% CI, 1.41 to 7.72), perceived non-efficacy (aOR, 6.21; 95% CI, 1.85 to 20.91) and being busy (aOR, 3.30; 95% CI, 1.21 to 9.01) were significantly and inversely associated with mumps vaccination. Recommendations from family doctors (aOR, 0.35; 95% CI, 0.17 to 0.71), living abroad when their children would be vaccinated (aOR, 0.10; 95% CI, 0.02 to 0.68) and the maternal age (aOR, 0.91; 95% CI, 0.85 to 0.96) were significant and positively associated with vaccination. Conclusions: In the absence of mandatory vaccinations, a public education campaign about mumps, their potential consequences and the nature and value of vaccination could improve the prevalence of mumps vaccination among children and prevent the consequences of this disease. Highlights: Identified serious public health problems such as meningitis and deafness related high incidence of mumps in Japan. Revealed impeding factors to raise immunization rate existed in current policy. Presented useful solution both at individual and policy levels.